KONTRIBUSI SEKTOR PERTANIAN DALAM PERTUMBUHAN DAN STABILITAS PRODUK DOMESTIK BRUTO - AMIRUDDIN SYAM; SAKTYANU K. DERMOREDJO (SOCA: Jurnal Sosial Ekonomi Pertanian, 2001)
This research aims to understand the contribution of agriculture sector in Gross DomesticProduct (GDP), its stability and its persistency. In GDP, agriculture sector, which is divided,by sub sector compare with other sectors in economics. The results shows: (1) Contributionof agriculture sector in the growth of GDP (1975-1995), the highest share was reached in1985 (21.05%). If it compare with the contribution of other sectors; (2) In the long term, oninterval 14-15, agriculture sector more resistance compared with manufacturing industrysector; however, in the short term agricultural sector is the most persistent. Compare withother sectors. Among agriculture sectors, forestry sub sector is the most persistent in longterm compare to other sectors, especially on interval 2-12, follow by food crops sub sector;and (3) Agriculture sector more stable compare with other sectors, except with mining andquarrying. Among agriculture sector, food crops sub sector has higher value in volatility andstability compare with other sectors.